Are Complex Skull Fractures Indicative of Either Child Abuse or Major Trauma in the Era of 3-Dimensional Computed Tomography Imaging?. Issue 1 (January 2022) - Metz, James B.; Otjen, Jeffrey P.; Perez, Francisco A.; Done, Stephen L.; Brown, Emily C. B.; Wiester, Rebecca T.; Jenny, Carole; Kelton, Megan C.; Ganti, Sheila N.; Feldman, Kenneth W.
Abstract : Objective: The aim of the study was to determine whether complex skull fractures are more indicative of child abuse or major trauma than simple skull fractures. Design: This is a retrospective chart and imaging review of children diagnosed with a skull fracture. Subjects were from 2 pediatric tertiary care centers. Children younger than 4 years who underwent a head computed tomography with 3-dimensional rendering were included. We reviewed the medical records and imaging for type of skull fracture, abuse findings, and reported mechanism of injury. A complex skull fracture was defined as multiple fractures of a single skull bone, fractures of more than 1 skull bone, a nonlinear fracture, or diastasis of greater than 3 mm. Abuse versus accident was determined at the time of the initial evaluation with child abuse physician team confirmation. Results: From 2011 to 2012, 287 subjects were identified by International Classification of Diseases, Ninth Revision, code. The 147 subjects with a cranial vault fracture and available 3-dimensional computed tomography composed this study's subjects. The average age was 12.3 months. Seventy four (50.3%) had complex and 73 (49.7%) had simple fractures. Abuse was determined in 6 subjects (4.1%), and a determination could not be made for 5 subjects. Adding abused children from 2013 to 2014 yielded 15 abused subjects. Twelve of the abused children (80%) had complex fractures; more than the 66 (48.5%) of 136 accidentally injured children ( P = 0.001; relative risk = 1.65 [1.21–2.24]). However, among children with a complex fracture, the positive predictive value for abuse was only 7%. Conclusions: Complex skull fractures frequently occur from accidental injuries. This study suggests that the presence of complex skull fractures should not be used alone when making a determination of abuse.